THE EFFECTS OF LIME AND PHOSPHATE FERTILIZATION IN CAMBISOLE SOIL ON DRY SEED WEIGHT OF SOYBEAN ( Glycine max L. ( Merr)) - Charles Silahooy (International Journal of Educational Research Excellence (IJERE), 2023)
Optimal soybean ( Glycine max L. ( Merr)) production can be done by liming and fertilizing. This research aims to obtain information about the effect of liming and phosphate fertilization in cambisol soil on the dry seed weight of soybean plants ( Glycine max L. ( Merr)). This research was carried out in Poka Village, Teluk Ambon Baguala District, Ambon City, taking place from February to July 2023. Soil and plant analysis was carried out at the Soil Laboratory, Faculty of Agriculture, Pattimura University. The experimental design used in this research was a Randomized Step Design (CRD) with a factorial pattern with three replications, where the parameter studied was the dry seed weight of soybean plants. The results of the study showed that the contribution made by liming to increasing the dry seed weight of soybean plants was relatively smaller compared to the larger phosphate (P2O5) fertilization.